2004
DOI: 10.1111/j.1439-0442.2004.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

The Lumbosacral Junction in Working German Shepherd Dogs – Neurological and Radiological Evaluation

Abstract: The clinical and radiological incidence of lumbosacral (LS) disease was studied on 57 German Shepherd dogs (GSDs) used in active service. The study included a clinical history, a neurological examination, and plain radiographs of the caudal lumbar vertebrae. The neurological examinations revealed lower back pain and/or neural deficits in 21 dogs, of which 14 had a history of pain or pelvic gait abnormalities. Radiographic findings were spondylosis at L7-S1, degeneration of L7-S1 disc, LS malalignment, transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…Radiographic positions were the same as those obtained for the previous study, 8 and radiographs obtained for the present study were compared with those obtained 3 years earlier. a One was obtained with the dog in lateral recumbency and the femurs perpendicular to the vertebral column; the other was obtained with the dog in dorsal recumbency, with the stifle joints abducted and the X-ray beam angled cranially by 7 o to 10 o so that it was parallel to the lumbosacral endplates.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Radiographic positions were the same as those obtained for the previous study, 8 and radiographs obtained for the present study were compared with those obtained 3 years earlier. a One was obtained with the dog in lateral recumbency and the femurs perpendicular to the vertebral column; the other was obtained with the dog in dorsal recumbency, with the stifle joints abducted and the X-ray beam angled cranially by 7 o to 10 o so that it was parallel to the lumbosacral endplates.…”
Section: Methodsmentioning
confidence: 94%
“…In a previous study, 8 results of neurologic and radiologic examinations of 60 working GSDs were reported. Thirty-three of these 60 dogs were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…OA commonly affects multiple joints in the dog [20], and many dogs in the present study had multiple joints affected with OA, including degenerative changes to the lumbosacral spine. Therefore, some dogs may have had a neuropathic pain component to their clinical signs, although degenerative changes to the lumbosacral spine seen radiographically are not highly correlated with clinical signs [21]. …”
Section: Discussionmentioning
confidence: 99%